Consumption, relative deprivation and mental health: evidence from hedonic consumption - Li, Hao; Zeng, Weihong (Frontiers in Public Health, 2025)
IntroductionIn recent years, relative deprivation related to consumption has sparked intense debate, particularly as the COVID-19 pandemic caused incalculable economic losses worldwide. However, the relationship between relative deprivation related to consumption and mental health remains largely unexplored. This study investigates how both vertical (household-level) and horizontal (household-to-household) relative deprivation related to consumption affect mental health, with a focus on hedonic consumption, and identifies underlying channels and moderating factors.MethodsWe analyze data from the China Family Panel Studies (CFPS) covering 88,144 observations from 2010 to 2018. Hedonic consumption is measured through expenditure on items such as jewelry, antiques, and entertainment, while consumption inequality is assessed using the Kakwani index. Mental health is evaluated using the CES-D and Kessler 6 scales. Ordinary least squares (OLS) and two-stage least squares (2SLS) methods are employed.ResultsOur findings show that reductions in hedonic consumption negatively impact mental health, with involuntary and sudden declines resulting in more pronounced deterioration. Furthermore, greater consumption inequality exacerbates mental health issues, and perceived unfair treatment amplifies this effect. Additionally, self-perception and trust levels are identified as key channels through which these effects. Furthermore, cultural variations and social capital are moderating roles to diminish the adverse mental health.ConclusionThis study advances our understanding of how relative deprivation related to consumption affects mental health and offers valuable insights for policymakers and practitioners aiming to address these challenges.